Damage and Failure Evolution Mechanism for Coal Pillar Dams Affected by Water Immersion in Underground Reservoirs. (6th January 2019) - Wang, Fangtian; Liang, Ningning; Li, Gang
Abstract : In coal mines, underground reservoir systems can increase the availability of water and are an effective technical approach for the protection and utilization of water resources. The stability of coal pillar dams is the key factor in the safety and stability of these underground water storage systems. However, coal pillar dams must operate in complex environments that combine dynamic-static superimposed stress fields and water immersion; moreover, coal pillar dams subjected to both stress and seepage are more susceptible to damage and even collapse. In this study, a seepage-stress coupling model of a coal pillar dam was constructed using the Universal Distinct Element Code (UDEC) simulation software. This model provides a platform for analyzing the characteristics of fracture development in surrounding rock in active mines and the coupled development of crack fields and seepage fields in coal pillar dams. Methods were developed for (1) calculating the water content for the coal pillar dam numerical simulation model and (2) reducing water immersion weakening. The maximum seepage width of a coal pillar dam subjected to water immersion was obtained, and a damage and failure evolution mechanism for coal pillar dams experiencing flooding was developed. The results provide a scientific basis for enhancing the stability control of coal pillar dams and are of great significance for realizing water conservation in coal mines.